Anthropometry and Body Composition of Adolescents in Macedonia - Myrtaj, Nazim; Maliqi, Arben; Gontarev, Seryozha; Kalac, Ruzdija; Georgiev, Georgi; Stojanoska, Biljana Bojadzieva (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2018)
The aim of this research was to determine the level of adiposity and obesity among Macedonian adolescents and to compare the results with previous studies conducted in this population, as well as those conducted in other populations. The sample included 2390 adolescents from four urban different regions of R. Macedonia aged between 11 to 18 years; 1238 males and 1152 females. Weight, height, waist, and hip circumference (WC, HC) as well as triceps, calf, subscapular, and suprailiac skinfold thickness (SFT) were measured. Body mass index (BMI), waist-to-hip ratio (WHR), waist-to-height ratio (WHtR), subscapular/triceps skinfold ratio (STR), and percentage body fat were computed. The prevalence of overweight and obesity defined by the IOTF children growth reference were calculated and age-dependent and gender-specific smoothed percentile curves for BMI and ROC curves were generated. The boys have statistically significantly higher values of WC, WHR and WHtR in all adult categories (except WHtR at 18 years old), greater body weight at the age of 12 to 18, and body weight 13 to 18 years (p<0.001). Weight, height and BMI are increasing with age in both, boys and girls, and decreases in girls. The level of adiposity of Macedonian adolescents has increased over the past 20 years and has reached the level of developed countries that face an obesity epidemic.
Keywords: Macedonian adolescents; Skinfold thickness; Waist circumference; Waist-to-height ratio; Waist-to-hip ratio.